2004
DOI: 10.1002/cne.20076
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic neuronal projections from the marginal layer of the rostral ventral medulla to the respiratory centers in rats

Abstract: The marginal layer (ML) that lines the ventral surface of the medulla oblongata (VMS) contains neurons thought to contribute to central chemoreception, the process by which systemic hypercapnia activates respiration. The transmitters and connectivity of ML neurons are poorly known. The present study focuses on a group of nonserotonergic ML neurons, often located in close proximity to the entry point of penetrating blood vessels. These neurons (approximately 300/brain) contain vesicular glutamate transporter2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 69 publications
4
58
0
Order By: Relevance
“…The neurons we identified are robustly chemosensitive, even in the absence of excitatory synaptic transmission, and they selectively innervate components of the central respiratory pattern generator (Mulkey et al, 2004;Rosin et al, 2006;Takakura et al, 2006). In vitro, we identified a corresponding subset of chemosensitive RTN neurons; furthermore, we showed that a pH-sensitive and K ϩ -selective background current contributes to this chemosensitivity, suggesting that it could be carried by TASK channels (Mulkey et al, 2004;Weston et al, 2004;Guyenet et al, 2005a,b;Stornetta et al, 2006).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The neurons we identified are robustly chemosensitive, even in the absence of excitatory synaptic transmission, and they selectively innervate components of the central respiratory pattern generator (Mulkey et al, 2004;Rosin et al, 2006;Takakura et al, 2006). In vitro, we identified a corresponding subset of chemosensitive RTN neurons; furthermore, we showed that a pH-sensitive and K ϩ -selective background current contributes to this chemosensitivity, suggesting that it could be carried by TASK channels (Mulkey et al, 2004;Weston et al, 2004;Guyenet et al, 2005a,b;Stornetta et al, 2006).…”
Section: Introductionmentioning
confidence: 62%
“…Historically, the region of the RTN in the rostroventrolateral medulla has been implicated in central chemoreception (Nattie, 1999;Feldman et al, 2003;Putnam et al, 2004;Nattie and Li, 2006), and our recent in vivo experiments have uncovered a population of pH-sensitive RTN neurons that represent excellent candidate neuronal substrates; those cells are glutamatergic (Mulkey et al, 2004;Weston et al, 2004;Guyenet et al, 2005a,b;Stornetta et al, 2006), and they express Phox2b , a transcription factor mutated in patients with congenital central hypoventilation syndrome in which chemical drive for breathing is selectively blunted (Amiel et al, 2003;Weese-Mayer et al, 2005a,b). In the present work, we used single cell RT-PCR to demonstrate that pH-sensitive RTN neurons recorded in vitro represent the cellular correlate of the glutamatergic and Phox2b-expressing chemoreceptors characterized in vivo (Mulkey et al, 2004;Weston et al, 2004;Guyenet et al, 2005a,b;Stornetta et al, 2006). Importantly, this identification allows direct experimental tests of the ionic basis for pH sensitivity in RTN chemoreceptor neurons in reduced preparations, and our characterization of phenotypic markers for these cells in mice will allow additional genetic exploration of the cellular and molecular bases for chemical control of breathing.…”
Section: Rtn Chemoreceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…RTN neurons are responsive to CO 2 , are glutamatergic, and have axonal projections anatomically appropriate for driving the respiratory network (43,44). Analysis of the hypercapnic response at different CO 2 concentrations revealed that Task2 −/− mice were hypersensitive to low CO 2 concentrations and showed an attenuated response at high CO 2 values.…”
Section: Discussionmentioning
confidence: 99%
“…They exhibited decreased ventilatory responses to hypercapnia on days 14 -15, suggesting a transient role for Kir2.2 in central chemosensitivity during postnatal development. Finally, null GLS1 mutant newborn mice had severe alterations in chemosensitivity to carbon dioxide (50), possibly related to dysfunction of glutaminergic neurons in central chemosensory areas (85).…”
Section: Mutant Newborn Mice With Abnormal Chemosensitivitymentioning
confidence: 99%